THE STUDY OF SUBORDINATE CLAUSES IN CHINA DAILY NEWSPAPER - Prabawati, Ni Luh Satya; Nugraha Putra, I Gusti Bagus Wahyu; Sidha Karya, I Wayan (Universitas Gunadarma, 2020)
Learning about subordinate clause it gives the understandings of the fuller descriptions of the main clause. This study aimed to find out the types of subordinate clause in complex sentences found in China Daily Newspaper. The data was collected through library research. This study used qualitative analysis method to describe and analysis the data found. The theory proposed by Miller (2002) is used to analyze the types of subordinate clause in complex sentences. The data analysis was presented through formal and informal method. Based on the result, there were three types of subordinate clause found in China daily Newspaper, namely relative clause, adverbial clause, and complement clause. This research found 61 subordinate clauses of complex sentences. Among the three types of subordinate clause, Relative clause is the most frequently found as modifier which 32 data or 52% and followed by Adverbial clause which 20 data or 33%. While the least frequently found is Complement clause which 9 data or 15%.